Pruritus in Autoimmune and Inflammatory Dermatoses - Zeidler, Claudia; Pereira, Manuel Pedro; Huet, Flavien; Misery, Laurent; Steinbrink, Kerstin; Ständer, Sonja (Frontiers in Immunology, 2019)
Pruritus in autoimmune and inflammatory dermatoses is a common symptom that can be severe and affect the quality of life of patients. In some diseases, itch is related to disorders activity and severity or may occur independent of the disease. Despite the high prevalence, the symptom is still underrated and there are only a few trials investigating the efficacy of drugs for disease-specific pruritus. In this review, the characteristics and possible pathomechanisms of pruritus in various dermatoses like bullous autoimmune diseases, connective tissue diseases as well as autoimmune-associated dermatoses (atopic dermatitis, psoriasis vulgaris) is illustrated. Additionally, studies analyzing the antipruritic treatment are discussed. Summarizing, the prevalence of pruritus in these diseases demonstrates the importance for symptom recognition and the need for an efficient antipruritic therapy.